Zola and the Physical Geography of War. (3rd July 2017) - White, Nicholas
ABSTRACT: Émile Zola's account of the Franco-Prussian War and the Commune, La Débâcle (1892), provides the basis for an account of the way in which the literary language of war speaks to the physical geography of mimetic fiction as broadly conceived, and in particular its precise concern for mud, earth, soil, and its wider concern for land and its borders.